Substituição de casca de soja por feno de tifton(Cynodon dactylon) em dietas a base de palma forrageira (Opuntia ficus-indica,Mill) para caprinos - SOUZA, Evaristo Jorge Oliveira de (2008)
The objective of this study was to evaluate the effects of replecement of soy bean hull by tifton hay (Cynodon dactylon) on intake, digestibility, nitrogen balance and microbial synthesis of goats feeding spineless cactus (Opuntia fícus-indica, Mill). Ten goats were used, half with 40 kg and others with 20 kg average live weigh. The experimental design was two 5 x 5 Latin Square (5 diet and 5 period). Diets consisted of spineless cactus, tifiton hay (0; 6,25; 12,5; 18,75 and 25%), soy bean meal, soy bean hull and mineral salt. The dry matter intake showed linear increase (P<0.05) with hay inclusion in the diets. However, with he increasing hay inclusion there were linear reduction (P<0.05) on dry matter digestibility. For each percent of hay inclusion there was a increase of 0,5 g of microbial protein. Nevertheless, there was no effect (P>0,05) on the microbial efficiency with increasing hay inclusion. It can be concluded that increasing hay inclusion in spineless cactus diets leaded to increase dry matter intake and microbial protein synthesis, but decreased nutrient digestibility.